Analisis Komparasi Profitabilitas Sebelum dan Sesudah Penawaran Umum Saham Perdana - WARDANI, SINTA; FITRIATI, RACHMA (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
The purpose of this study is to know how the profitability (gross profit margin, operating profit margin, return on asset, return on equity dan return on investment) of PT Adhi Karya, as an object of this study, before and after IPO 2004-2008 period. This research is qualitative descriptive interpretive. The data were collected from company financial statement 2000 – 2008 which four years before and after the IPO and excluded 2004 as the year of IPO. The research result showed that only gross profit margin, operating margin dan net profit margin which have a better performance after IPO. From Kruskall Wallis test profitability has a better finance performance after IPO.